Odpowiedzi

2010-02-03T17:00:26+01:00
A) 2x - y = 5
2x=5+y /:2
x=2,5+1/2y
b) ⅓y = x - 3
-x=-3-1/3y /:(-1)
x=3+1/3y
c) 3(x-y) = 2x
3x-3y=2x
3x-2x=3y
x=3y
d) ⅔x = ¾y /*3/2
x=9/8
e) 4x + 2y = 1
4x=1-2y /:4
x=4-8y
f) 6x - ⅔y = 2
6x=2+2/3y /:6
x=1/3+4y
1 5 1
Najlepsza Odpowiedź!
2010-02-03T17:39:33+01:00
A)
2x - y = 5
2x = 5 + y /: 2
x = 5/2 + y/2

b)
⅓y = x - 3 /*3
x = 1/3y + 3

c)
3(x-y) = 2x
3x - 3y = 2x
3x -2x = 3y
x = 3y

d)
⅔x = ¾y / * 3/2
x = 9/8y

e)
4x + 2y = 1
4x = 1 - 2y /:4
x = 1/4 - 1/2 y

f)
6x - ⅔y = 2 /*3
18x - 2y = 6
18x = 6 + 2 y /:18
x = 1/3 + 1/9 y
1 5 1